2022
DOI: 10.1155/2022/4932856
|View full text |Cite
|
Sign up to set email alerts
|

Results of the Pinhole Test Correlate with Hybrid Contact Lens Visual Acuity in Patients with Visual Impairment due to Corneal Diseases

Abstract: Introduction. Trial rigid lens fitting is considered the best approach to determine whether the correction of residual defocus and irregular astigmatism might improve the visual acuity in patients with corneal disorders including keratoconus. This study aimed to analyze the correlation between hybrid lenses and pinhole visual acuity (VA). Methods. Patients undergoing hybrid contact lens fitting at the Hygeia Clinic, Poland, were included. The VA of each patient was assessed as decimal Snellen fractions under t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…59 In another study, the pinhole test was considered as a simple predictor of improvement with hybrid contact lenses (rigid center surrounded by a soft lens skirt). 27 The improvement in VA with the pinhole test was correlated positively with VA with a hybrid contact lens in patients with keratoconus and other corneal diseases and was better than with spherocylindrical correction. 27 Finally, the pinhole test may be used to identify a poor refraction, for example, if the spectacle-corrected VA is 6/7.5 and the pinhole improves this to 6/6, perhaps astigmatism may have been missed.…”
Section: Applications In Clinical Vision Sciencementioning
confidence: 82%
See 2 more Smart Citations
“…59 In another study, the pinhole test was considered as a simple predictor of improvement with hybrid contact lenses (rigid center surrounded by a soft lens skirt). 27 The improvement in VA with the pinhole test was correlated positively with VA with a hybrid contact lens in patients with keratoconus and other corneal diseases and was better than with spherocylindrical correction. 27 Finally, the pinhole test may be used to identify a poor refraction, for example, if the spectacle-corrected VA is 6/7.5 and the pinhole improves this to 6/6, perhaps astigmatism may have been missed.…”
Section: Applications In Clinical Vision Sciencementioning
confidence: 82%
“…58 The pinhole test has also been shown useful in estimating the potential improvement over spherocylindrical correction with hybrid contact lenses in keratoconus and other corneal diseases. 27 Although the pinhole test is used often in clinical practice, it has not been described extensively. 59,60 Kumar et al found that the improvement in the pinhole test is correlated with the magnitude of spherical equivalent refraction (Spearman r = 0.68, P < .001) and concluded that the pinhole occlusion is a valid gauge of refractive error in Rapid Assessment of Avoidable Blindness surveys.…”
Section: Pinhole Testmentioning
confidence: 99%
See 1 more Smart Citation